On the pedagogy of pharmacological communication: a study of final semester health science students. Issue 1 (December 2015) - Zetterqvist, Ann; Aronsson, Patrik; Hägg, Staffan; Kjellgren, Karin; Reis, Margareta; Tobin, Gunnar; Booth, Shirley
Abstract Background There is a need to improve design in educational programmes for the health sciences in general and in pharmacology specifically. The objective of this study was to investigate and problematize pharmacological communication in educational programmes for the health sciences. Methods An interview study was carried out where final semester students from programmes for the medical, nursing and specialist nursing in primary health care professions were asked to discuss the pharmacological aspects of two written case descriptions of the kind they would meet in their everyday work. The study focused on the communication they envisaged taking place on the concerns the patients were voicing, in terms of two features: how communication would take place and what would be the content of the communication. A phenomenographic research approach was used. Results The results are presented as outcome spaces, sets of categories that describe the variation of ways in which the students voiced their understanding of communication in the two case descriptions and showed the qualitatively distinct ways in which the features of communication were experienced. Conclusions The results offer a base of understanding the students' perspectives on communication that they will take with them into their professional lives. We indicate that there is room for strengthening communication skills in the field of pharmacology, integrating them into programmes of education, by more widely implementing a problem-based, a case-oriented or role-playing pedagogy where final year students work across specialisations and there is a deliberate effort to evoke and assess advanced conceptions and skills.